Treatment Outcomes of 9,994 Patients With Extensive-Disease Small-Cell Lung Cancer From a Retrospective Nationwide Population-Based Cohort in the Korean HIRA Database - Lee, Jung Soo; Kim, Seoree; Sung, Soo-Yoon; Kim, Yeo Hyung; Lee, Hyun Woo; Hong, Ji Hyung; Ko, Yoon Ho (Frontiers in Oncology, 2021)
To investigate the efficacy of irinotecan-based (IP) and etoposide-based (EP) platinum combinations, and of single-agent chemotherapy, for treatment of extensive-disease small cell lung cancer (ED-SCLC), we performed a large-scale, retrospective, nationwide, cohort study. The population data were extracted from the Health Insurance Review and Assessment Service of Korea database from January 1, 2008, to November 30, 2016. A total of 9,994 patients were allocated to ED-SCLC and analyzed in this study. The primary objectives were to evaluate the survival outcomes of systemic first-line treatments for ED-SCLC. For first-line treatment, patients who received IP showed a better PFS of 8.9 months (95% confidence interval [CI], 8.50–9.40) than those who received EP, who had a PFS of 6.8 months (95% CI, 6.77–6.97, P < 0.0001). In terms of OS, IP was superior to EP (median OS, 10.8 months; 95% CI, 10.13–11.33 vs. 9.5 months; 95% CI, 9.33–9.73; P < 0.0001). Taken together, in the Korean population, first-line IP combination chemotherapy had significantly favorable effects on OS and PFS.